2023
DOI: 10.17221/288/2022-pse
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on suitability of growing ginseng (Panax ginseng Meyer) in western Himalayan region

Abstract: Panax ginseng Meyer (family Araliaceae) has been used in oriental medicine for over 2000 years having a long history as a general tonic promoting health, and it is believed to be a panacea and to promote longevity. It is distributed in 35 countries, mainly in Eastern Asia (especially in Japan, Korea, northeastern China, Bhutan, and East Siberia) and in Northern America, usually in cooler climates (Ryu et al. 2012). Also, very valuable wild species of ginseng are found in India, Nepal, and Myanmar with characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The literature regarding the optimization of ginseng cultivation and its adaptability in various environments is rather poor. According to Walia et al [ 51 ], the optimum temperature for P. ginseng plant growth is 16–28 °C. Mork et al [ 52 ] had previously found that during the early vegetive stages, the ideal air temperature ranges from 10 to 20 °C, and from the flowering stage and afterwards from 21 to 25 °C.…”
Section: Tobacco Alternative Cropsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature regarding the optimization of ginseng cultivation and its adaptability in various environments is rather poor. According to Walia et al [ 51 ], the optimum temperature for P. ginseng plant growth is 16–28 °C. Mork et al [ 52 ] had previously found that during the early vegetive stages, the ideal air temperature ranges from 10 to 20 °C, and from the flowering stage and afterwards from 21 to 25 °C.…”
Section: Tobacco Alternative Cropsmentioning
confidence: 99%
“…Overall, it prefers cool-temperate climates as high temperatures and solar radiation can cause scorches and sunburn on its leaves [ 53 ]. Ginseng favors well-draining, fertile, acidic soils with pH close to 5 [ 51 , 54 ]. Soil fertility, and specifically the availability of zinc, manganese, iron, and copper, is crucial for its cultivation [ 55 ].…”
Section: Tobacco Alternative Cropsmentioning
confidence: 99%
See 1 more Smart Citation